Infrastructural impediments faced by Children with Special Needs in Primary Government Schools - Chelsea Ann Scolt (International Journal of Psychosocial Rehabilitation, 2020)
Education is a basic right of children across the globe. In India the Right to Education became a fundamental right under Article 21A of the constitution with the emergence of the 86th amendment in 2002. Sarva Shiksha Abhiyan (SSA) developed between 2000-2001 aims towards the achievement of Universal Elementary Education with the objective of providing equal opportunities to all children in the sphere of education. While the Right to Education has been clearly established across the country, the accessibility to this right remains a question mark for certain children in India. The focus of this paper is on the accessibility to various governmental educational institutions by students with disabilities. The Right to Education Act (2009) and the Rights of Persons with Disabilities Act (2016) provide for measures to ensure zero discrimination to students with disabilities and measures to ensure the accessibility of education to all children. Yet UNESCO reports in 2019 state that 75% of children with disabilities do not attend schools in India. A major cause behind such statistics is the lack of conducive infrastructure for children with special needs. While schools are available they still aren’t accessible to students with disabilities and this poses as a major challenge to the educational system of our country. Hence the aim of this paper is to understand the existing infrastructural impediments in the primary schools of West Bengal. A mixed method approach was utilized to execute this study, while structured interview schedules and in-depth interview guides aided in obtaining the data required to understand the current situation for students with disabilities and provide solutions to amend the same.